Use of deep eutectic solvents in the enzyme catalysed production of ethyl lactate. (September 2019) - Arıkaya, Azime; Ünlü, Ayşe Ezgi; Takaç, Serpil
Graphical abstract: Highlights: Deep eutectic solvents are promising solvents for the esterification of lactic acid. Choline chloride:Glycerol (1:2) provided 28.7% yield of ethyl lactate. Choline chloride:Glycerol (1:2) enhanced lipase enzyme activity by 3-fold. Choline chloride:Glycerol (1:2) partially repressed inhibition effects of substrates. Abstract: The use of deep eutectic solvents (DESs) in the lipase-catalysed esterification of lactic acid with ethanol was explored by screening several DESs. Choline chloride:glycerol (1:2) was the most effective DES and provided 28.7% yield of ethyl lactate under the following conditions: 10% (v/v) of water content in DES, 3 M of initial lactic acid concentration, 5 M of initial ethanol concentration, 30 mg/mL of enzyme concentration, 50 °C temperature and 200 rpm agitation rate. Individual and combined effects of the reaction medium components on the enzyme activity were investigated and it was discovered that DES stimulated the enzyme activity while reactants inhibited it. A kinetic model that obeys the Ping-Pong Bi-Bi mechanism with ethanol inhibition was suggested. The kinetics parameters were determined as rmax =0.401 mol/L h, the Michaelis constants KA  = 1.657 mol/L and KB  = 0.799 mol /L, the inhibition constant KiB =0.156 mol/L. The model reasonably predicted the experimental data. The activation energy was found to be 43.28 kJ/mol. Mass transfer limitations in the reaction medium were negligible. The results are promising for further studies that will research on the use of green solvents in enzyme-catalysed lactic acid esterification reactions.